The Implementation of Problem Based Learning Model to Improve Student’s Motivation and Critical Thinking - Hestiningtyas Yuli Pratiwi; Nurul Ain; Helena Jelita Igut (Universitas Lambung Mangkurat, 2019)
The research aims to analyze the quality of the learning process using the Problem-Based Learning (PBL) model to find out the improvement of student’s motivation and critical thinking skills. It is a classroom action research conducted in two cycles, cycle I consist of 4 meetings, and cycles II consists of 3 meetings, with the topics of Temperature, Expansion, and Heat. The subjects of the research were 34 students on grade VII in one of the junior high schools in Malang. Instruments used to measure the implementation of learning PBL model using the form of implementation sheet following the lesson plan, tools to measure motivation using a poll and to measure the critical thinking skill, and researchers use essay questions. The implementation of the PBL model in the cycle, I was 72.9% and was classified as a good qualification; while in cycle II, it was 91.2% and was classified as a very good qualification. The analysis of student’s learning motivation in pre-cycle was 56%, was classified as a quite good qualification, cycle I was 67.2%. I was classified as a quite good qualification, while in Cycle II, it was 87.2% and was classified as good qualification. The analysis of student’s average critical thinking skills in pre-cycle was 44.12% and was classified lack of good qualification, cycle I was 76.4% and was classified as a quite good qualification; while in cycle II it was 88.4% and was classified as good qualification. The results showed that the PBL model successfully improved motivation and critical thinking skills of students beginning the pre-cycle, cycle I, and cycle II.